KERAGAMAN TANAMAN EDAMAME (Glycine max L. Merrill) VARIETAS RYOKO TERHADAP PERLAKUAN JARAK TANAM DAN DOSIS PUPUK KANDANG AYAM - Yudi Yusdian; Karya; Santoso, Joko; Erfan; Joestia Zhahiran, Alyanisa (Program Studi Agroteknologi Faperta UNIBBA, 2025)
This research aims to determine the growth and yield response of Edamame (Glycine max L. Merrill) cv. Ryoko to plant spacing and chicken manure dosage. This research was conducted in Margahurip Village, Banjaran District, Bandung Regency, West Java Province with an altitude of 800 m above sea level, pH 6.06 (slightly acidic) and rainfall of 2,481 mm/year. This research used a factorial Randomized Block Design (RBD) method with 3 replications. First factor: Planting Distance (j1= 30 cm x 10 cm, j2= 30 cm x 20 cm, j3= 30 cm x 30 cm). Second factor: Chicken Manure Fertilizer Dosage (k1 = 0 tons/ha, k2 = 10 tons/ha, k3 = 20 tons/ha). The results of the research showed that there was an independent effect in the 30 cm x 30 cm planting spacing treatment which had a better influence on plant height, number of branches, number of planted pods and weight of planted pods. Meanwhile, the chicken manure dose of 10 tonnes/ha had a better effect on the number of pods planted and the weight of the pods planted.